The frequency of antlerless females among Svalbard reindeer - Jacobsen, Bente W.; Colman, Jonathan E.; Reimers, Eigil (Rangifer, 1998)
The distribution of females with no, one and two antlers was recorded during July 1994 in Svalbard reindeer, Rangifer tarandus platyrhynchus, and compared wirh 1974 data from Reimers (1993) and Larsen (1977). On Reinsdyrflya, 50% of the females were anrlerless, 16% one antlered and 34% rwo antlered. In Nordenskiold Land, 2% of the females were antlerless, 1% one antlered and 97% two antlered. These percentages have not changed since Reimers' study in 1974 in Reinsdyrflya (Chi square 2= 1.16, P > 0.05) and Nordenskiold Land (Chi square 2 = 1.69, P > 0.05). The reason for the high frequency of anrlerless females on Reinsdyrflya is not understood.